2022
DOI: 10.1001/jamanetworkopen.2022.46915
|View full text |Cite
|
Sign up to set email alerts
|

Estimated BNT162b2 Vaccine Effectiveness Against Infection With Delta and Omicron Variants Among US Children 5 to 11 Years of Age

Abstract: ImportanceData describing the vaccine effectiveness (VE) and durability of BNT162b2 among children 5 to 11 years of age are needed.ObjectiveTo estimate BNT162b2 VE against SARS-CoV-2 infection among children aged 5 to 11 years during Delta and Omicron variant–predominant periods and to further assess VE according to prior SARS-CoV-2 infection status and by sublineage during the Omicron variant–predominant period.Design, Setting, and ParticipantsThis test-negative case-control study was conducted from November … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 15 publications
(55 reference statements)
4
29
0
Order By: Relevance
“… 26 , 27 Studies were primarily done in high-income countries (eg, the USA, Canada, and Israel), and assessed a complete primary schedule of BNT162b2 vaccine (n=46 [90%]). Three (6%) studies only assessed the effect of a single dose of either BNT162b2 or mRNA-1273, 28 , 29 , 30 and nine (18%) studies assessed the effect of a monovalent 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 or bivalent (BNT162b2 bivalent [against original strain or omicron BA.4 or BA.5]) 39 booster vaccination ( appendix 1 pp 26–33 ). Participants' age was in line with the authorised age group (ie, 5–11 years for studies on BNT162b2 or BNT162b2 bivalent and 6–11 years for studies on mRNA-1273; appendix 1 pp 26–33 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 26 , 27 Studies were primarily done in high-income countries (eg, the USA, Canada, and Israel), and assessed a complete primary schedule of BNT162b2 vaccine (n=46 [90%]). Three (6%) studies only assessed the effect of a single dose of either BNT162b2 or mRNA-1273, 28 , 29 , 30 and nine (18%) studies assessed the effect of a monovalent 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 or bivalent (BNT162b2 bivalent [against original strain or omicron BA.4 or BA.5]) 39 booster vaccination ( appendix 1 pp 26–33 ). Participants' age was in line with the authorised age group (ie, 5–11 years for studies on BNT162b2 or BNT162b2 bivalent and 6–11 years for studies on mRNA-1273; appendix 1 pp 26–33 ).…”
Section: Resultsmentioning
confidence: 99%
“… 40 , 43 , 44 , 47 All reported a substantial reduction in vaccine effectiveness against SARS-CoV-2 infections of at least 15% from the timepoint of first measurement after two-dose vaccination to the timepoint of last measurement ( appendix 1 p 40 ). One study 32 reported vaccine effectiveness against omicron infections after the third dose (vaccine effectiveness 55% [50–60]) and reported no effect of waning protection up to 4 months after the booster.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, a further increase in parental hesitancy levels with further reduction of COVID-19 immunization rates in children aged 5–11 years may be evidenced by of the impact of the Omicron SARS-CoV-2 variants and the position taken by some countries regarding the administration of COVID-19 vaccines in children aged 5–11 years. Studies carried out after the emergence of the Omicron variant in December 2021 and published some months later showed that the effectiveness of the BNT162b2 vaccine in 5–11 year-old children was significantly reduced compared to the effectiveness shown in the studies performed for emergency authorization and carried out when the wild virus or earlier variants, including the Delta variant, were circulating [ 45 , 46 , 47 , 48 , 49 ]. A retrospective study carried out in Italy between 17 January and 13 April 2022 which enrolled 2,965,918 immunized children and 1,441,166 controls showed that the effectiveness of the recommended two doses of the BNT162b2 vaccine against infection was only 29.4% and 27.4%, respectively, in fully vaccinated and partially vaccinated children [ 50 ].…”
Section: Discussionmentioning
confidence: 99%